Hydrogenation catalyst for coal-based cracking of C9 < + > component and preparation method thereof
Through the combination of the modified support and organic complexing agent, an efficient hydrogenation catalyst is prepared, which solves the problem of insufficient catalytic activity of hydrodesulfurization of coal-based C9+ oil products in the prior art, and significantly improves the catalytic performance and efficiency.
Patent Information
- Application Number
- CN202411265799.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing hydrodesulfurization catalysts have poor catalytic activity when hydrodesulfurizing coal-based C9+ oil products, making it difficult to effectively utilize the catalytic potential of coal-based C9+ components.
Using modified support, including pseudo-thin hydrotalcite and magnesium hydrotalcite, combined with active metal elements and organic complexing agents, hydrogenation catalysts are prepared by impregnation and calcination, pH value and calcination conditions are adjusted, and the physical and chemical properties of the catalyst and the active metals are optimized. Dispersibility.
It significantly improves the catalytic performance and activity of the hydrogenation catalyst, improves the hydrodesulfurization efficiency of coal-based C9+ components, reduces the bromine price, and extends the service life of the catalyst.
Smart Images

Figure BDA0005037096210000101 
Figure BDA0005037096210000111 
Figure BDA0005037096210000112
Abstract
Description
Technical Field
[0001] The present invention relates to the field of hydrogenation catalysts, and in particular to a hydrogenation catalyst for coal-based cracking of C9+ components and a preparation method thereof. Background Art
[0002] The cracked C9+ component is a by-product of the steam cracking ethylene production unit. Currently, it is mostly sold directly as a relatively cheap primary raw material. Only a small number of units process it as a gasoline blending component or solvent oil. Because its components are extremely complex and very dispersed, it is rich in more than 200 components such as dicyclopentadiene and indene, has good solubility and high octane number, and can be used as a blending component of aromatic solvent oil and high-octane gasoline after modification. Therefore, the hydrodesulfurization technology of the cracked C9+ component occupies an important position in the comprehensive utilization of the C9+ component, and has broad application prospects due to the high added value of the products after hydrodesulfurization.
[0003] The cracking C9+ components mainly include petroleum-based C9+ oil products and coal-based C9+ oil products. Among them, petroleum-based C9+ oil products are mainly C9 aromatics (alkenyl aromatics) accounting for 46.29%, and dicyclopentadiene (DCPD) accounting for 15.78%. Coal-based C9+ oil products are different from petroleum-based C9+ oil products. The largest proportion of its composition is methyl indane, with a content of 37.251%, which mainly affects the density of the oil products; the diene content is 4.179%, which mainly affects the oxidation stability of the oil products, and the direct indicator reflected is the high bromine value.
[0004] However, most of the current research on hydrodesulfurization catalysts for cracking C9+ components focuses on petroleum-based C9+ oils, while coal-based C9+ oils are rarely involved. The difference in the components between the two leads to poor performance of hydrodesulfurization catalysts used for petroleum-based C9+ oils when used for hydrodesulfurization of coal-based C9+ oils.
[0005] Based on this, how to comprehensively design and optimize the carrier, active metal and the interaction between the two of the catalyst used for the hydrodesulfurization of coal-based C9+ oil products so that the resulting hydrodesulfurization catalyst has better physical and chemical properties, thereby having higher catalytic activity for the hydrodesulfurization of coal-based C9+ oil products, is one of the important technical problems that need to be solved in this field. Summary of the invention
[0006] The main purpose of the present invention is to provide a hydrogenation catalyst for coal-based cracking C9+ components and a preparation method thereof, so as to solve the problem that the hydrodesulfurization catalyst in the prior art has poor catalytic activity during the hydrodesulfurization of coal-based C9+ oil products.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a hydrogenation catalyst for coal-based cracking C9+ components, comprising: step S1, preparing a modified carrier, the modified carrier comprising pseudo-boehmite and magnesium-aluminum hydrotalcite; step S2, preparing a first impregnation solution and adding the modified carrier thereto, the first impregnation solution comprising an active metal element and an organic complexing agent; step S3, adding a pH regulator to the first impregnation solution to obtain a second impregnation solution with a pH of 9 to 11; step S4, impregnating the modified carrier in the second impregnation solution, and obtaining a hydrogenation catalyst for coal-based cracking C9+ components after solid-liquid separation, drying and roasting; the active metal element comprises Mo and at least one transition metal element other than Mo, and the molar ratio of the active metal element to the organic complexing agent is 1:(0.02 to 1.5).
[0008] Furthermore, the organic complexing agent is selected from one or more of urea, triethanolamine and citric acid, and the transition metal is selected from one or more of Ni, Co and Zn.
[0009] Furthermore, the active metal elements are Mo and Ni, the organic complexing agent is triethanolamine and / or urea, and the molar ratio of Mo to triethanolamine and / or urea is 1:(0.05-0.1); or, the active metal elements are Mo and Co, the organic complexing agent is citric acid, and the molar ratio of Co to citric acid is 1:(0.1-1).
[0010] Furthermore, step S1 also includes: step S1-1, mixing pseudo-boehmite, magnesium-aluminum hydrotalcite and an extrusion aid uniformly to obtain a first mixed material; step S1-2, adding acid solution to the mixed material to obtain a second mixed material; step S1-3, the second mixed material is successively molded, dried and calcined to obtain a modified carrier; preferably, based on the weight of the pseudo-boehmite as 100%, the amount of magnesium-aluminum hydrotalcite added is 10% to 20%; preferably, the calcination temperature is 300°C to 600°C.
[0011] Furthermore, the calcination in step S1-3 is a first-stage calcination, a second-stage calcination and a third-stage calcination carried out in sequence, and: the temperature of the first-stage calcination is 300°C to 350°C; the temperature of the second-stage calcination is 400°C to 420°C; the temperature of the third-stage calcination is 500°C to 600°C; the time for the first-stage calcination, the second-stage calcination and the third-stage calcination is each independently 2h to 4h.
[0012] Furthermore, based on 100% weight of pseudo-boehmite, the amount of extrusion aid added is 5% to 8%, and the amount of acid solution added is 75% to 80%; preferably, the extrusion aid is sesbania powder and / or methyl cellulose; preferably, the mass fraction of the acid solution is 1% to 10%, and the acid solution is citric acid and / or nitric acid.
[0013] Furthermore, the pH regulator in step S3 is aqueous ammonia; the impregnation in step S4 is dynamic impregnation, and the dynamic impregnation is achieved by using a rotary evaporator.
[0014] Furthermore, in step S4, the drying temperature is 100-120° C., and the time is 2-12 hours; the calcination temperature is 420-470° C., and the time is 2 hours to 3 hours.
[0015] Another aspect of the present invention provides a hydrogenation catalyst for coal-based cracking of C9+ components. The hydrogenation catalyst for coal-based cracking of C9+ components is prepared by the above-mentioned preparation method.
[0016] Furthermore, the specific surface area of the hydrogenation catalyst for coal-based cracking C9+ components is 150 g / cm 3 ~170g / cm 3 , the proportion of medium and strong acids is 45% to 55%.
[0017] By applying the technical solution of the present invention, a simple and easy preparation method is adopted for catalytic hydrodesulfurization of coal-based cracking C9+ components, which effectively improves the physical and chemical properties of the catalyst carrier and improves the problem of strong interaction between the carrier and the active metal, thereby significantly improving the catalytic performance of the hydrogenation catalyst when used for catalytic hydrodesulfurization reactions of coal-based cracking C9+ components. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As described in the background art, the hydrodesulfurization catalyst in the prior art has the problem of poor catalytic activity in the hydrodesulfurization of coal-based C9+ oil products. In order to solve the above technical problems, the present invention provides a method for preparing a hydrogenation catalyst for coal-based cracking C9+ components, comprising: step S1, preparing a modified carrier, the modified carrier comprising pseudo-boehmite and magnesium aluminum hydrotalcite; step S2, preparing a first impregnation liquid and adding the modified carrier thereto, the first impregnation liquid comprising an active metal element and an organic complexing agent; step S3, adding a pH regulator to the first impregnation liquid to obtain a second impregnation liquid with a pH of 9 to 11; step S4, impregnating the modified carrier in the second impregnation liquid, and after solid-liquid separation, drying and roasting, obtaining a hydrogenation catalyst for coal-based cracking C9+ components; the active metal element comprises Mo and at least one transition metal element other than Mo, and the molar ratio of the active metal element to the organic complexing agent is 1: (0.02 to 1.5).
[0020] Pseudo-boehmite (i.e., monohydrated aluminum oxide, AlOOH·nH2O, n=0.08-0.62) has good structure, mechanical properties and relatively low cost after calcination, can provide high specific surface area, and can improve catalyst performance by interacting with active metals. However, despite its good mechanical strength, the strong interaction with transition metals leads to incomplete sulfidation of the catalyst and low hydrodesulfurization activity. In the preparation method provided by the present invention, pseudo-boehmite and magnesium aluminum hydrotalcite are first used to prepare a modified carrier. Among them, the structure of magnesium aluminum hydrotalcite is MgAl-LDHs, and due to the particularity of its composition and structure, it has a large specific surface area and acid-base centers of different strengths, which can improve the physical and chemical properties of the alumina carrier; at the same time, magnesium aluminum hydrotalcite contains alkaline earth metal Mg, so when it is used as a carrier component, it can weaken the strong interaction between the carrier and the active component, making the active metal easy to activate, and ultimately significantly improving the structure and performance of the catalyst.
[0021] In the process of preparing the impregnation solution, the present invention also adds an organic complexing agent to cooperate with the active metal element, and adjusts the pH under the condition that the modified carrier, the organic complexing agent and the active metal element exist at the same time, so as to further weaken the strong interaction between the carrier and the active component, and at the same time improve the uniformity of the dispersion of the active metal element thereon, so that the obtained hydrogenation catalyst for coal-based cracking C9+ components exhibits higher catalytic activity. And, the catalyst system provided by the present invention must contain the Mo element, because compared with other active metals, Mo has special electronic properties (i.e., unfilled d electron orbits) and geometric properties (i.e., when forming crystals, it is mostly a body-centered cubic structure), which can better cooperate with the modified carrier, thereby exhibiting higher catalytic activity; and the present invention also adds at least one transition metal element other than Mo, so as to improve the electronic structure and dispersibility of the active component, thereby promoting the formation of active sites.
[0022] It is worth mentioning that for the catalyst used for coal-based cracking C9+ components, the present invention strictly limits the molar ratio of active metal elements to organic complexing agents. This is because the coal-based cracking C9+ components themselves have complex components and high content of indane and its derivatives. When the molar ratio of active metal elements to organic complexing agents is 1: (0.02~1.5), the solubility of active metals can be improved, thereby strengthening the interaction between active metals and ultimately weakening the strong interaction between active metals and carriers, making it easy for active metals to be activated and the cracking reaction more complete.
[0023] Also, during the impregnation process, for traditional hydrodesulfurization catalysts, in order to improve their catalytic performance, it is usually achieved by increasing the metal loading, but when the metal loading reaches a certain level, it is necessary to face the problem that the solubility of the metal salt does not meet the design requirements. In order to achieve the target loading, the preparation of the catalyst needs to go through a multi-step impregnation process, and the preparation method of the multi-step impregnation leads to a cumbersome preparation process, increased costs, and the dispersion of the active metal of the catalyst finally obtained is not ideal. The present invention, by adding a complexing agent, forms a complex with the complexing agent under complexation, thereby enhancing the stability of the impregnation solution, increasing the solubility of the active metal, and obtaining a high-loaded catalyst, that is, only one impregnation completes the full loading of the active metal, effectively shortens the production process cycle, and improves the commercial value.
[0024] The preparation method provided by the present invention has a simple process, and the raw materials used are easy to obtain, the cost is low, and each raw material will not have adverse effects on the environment and equipment, so as to facilitate better industrialization and large-scale application. In practical applications, the magnesium-aluminum hydrotalcite in step S1 is added in the form of hydrotalcite raw powder, which is not only simple to operate, but also effectively saves production costs.
[0025] Furthermore, the inventors have selected one or more of urea, triethanolamine and citric acid as the organic complexing agent through a large number of experiments. Compared with the types of organic complexing agents commonly used in the preparation of hydrogenation catalysts (including organic amines and organic acids), for the raw material of coal-based cracking C9+ component, urea, triethanolamine and citric acid are used as the raw materials for the preparation of the catalyst. The resulting catalyst exhibits higher catalytic activity. Specifically, triethanolamine and urea are alkaline. When they are added to a solution containing active metal elements, the pH value of the impregnation solution can be increased, thereby corroding the catalyst carrier and increasing its specific surface area, that is, increasing the active sites; secondly, the hydroxyl and amino groups on triethanolamine and urea can form complexes with the active metals to avoid the active metal components being directly loaded on the catalyst carrier, so as to weaken the interaction between the active metal components and the catalyst carrier, so that more hydrogenation centers are formed on the catalyst carrier, the effective utilization rate of the active metal components is improved, and the activity of the catalyst is further improved. More importantly, for the raw material of coal-based cracking C9+ component, compared with other organic amine complexing agents, urea and triethanolamine can make the formed catalyst have excellent performance for selective saturation of indane and its derivatives. Citric acid can interact with the hydroxyl groups on the surface of the carrier through hydrogen bonding, improve the distribution of oxidized hydroxyl groups on the surface of the carrier, and then weaken the strong interaction between the carrier and the active metal, and improve the dispersion and sulfidation degree of the active metal elements; at the same time, citric acid can also effectively improve the surface acidity of the catalyst, improve the dispersion of the metal on the surface of the catalyst, make it easier to be sulfided, and finally significantly improve the hydrodesulfurization performance of the catalyst. And, for the raw material of coal-based cracking C9+ component, compared with other organic acid complexing agents, citric acid can chelate with active metal ions to form a complex, prevent the metal component from agglomerating, inhibit the formation of spinel, and enhance the hydrodesulfurization performance of the formed catalyst, extending the service life of the catalyst. Transition metals other than Mo are preferably selected from one or more of Ni, Co and Zn. After a large number of experiments, the inventors found that compared with other types of transition metals, Ni, Co and Zn can better cooperate with Mo elements, thereby optimizing their electronic structure and improving their catalytic activity in the hydrodesulfurization reaction of coal-based cracking C9+ components.
[0026] In the actual experimental process, Mo is added in the form of ammonium heptamolybdate or molybdenum trioxide (calculated as oxide, its content in the raw material medicine ranges from 20wt% to 30wt%); Ni is added in the form of nickel nitrate or basic nickel carbonate, and Co is added in the form of cobalt nitrate or basic cobalt carbonate (calculated as oxide, the content of Ni and Co in the raw material medicine independently ranges from 3wt% to 7wt%).
[0027] In several typical embodiments, the active metal elements are Mo and Ni, the organic complexing agent is triethanolamine and / or urea, and the molar ratio of Mo to triethanolamine and / or urea is 1:(0.05-0.1); or, the active metal elements are Mo and Co, the organic complexing agent is citric acid, and the molar ratio of Co to citric acid is 1:(0.1-1). After a large number of experiments and comparisons, the inventor optimized the matching selection of active metal elements and organic complexing agents to the above scheme, and also further optimized the molar ratio of specific metal elements to organic complexing agents. Under the conditions of the above scheme, a hydrogenation catalyst for coal-based cracking C9+ components with superior structural properties, physicochemical properties and catalytic activity was obtained, which showed higher reaction activity in the hydrodesulfurization reaction of coal-based cracking C9+ components, and the organic sulfur content and bromine value of coal-based cracking C9+ components were significantly reduced.
[0028] In the preparation process of the modified carrier, further, step S1 also includes: step S1-1, mixing pseudo-boehmite, magnesium aluminum hydrotalcite and extrusion aid uniformly to obtain a first mixed material; step S1-2, adding acid solution to the mixed material to obtain a second mixed material; step S1-3, the second mixed material is sequentially formed, dried and calcined to obtain a modified carrier. The present invention further provides the above-mentioned specific process flow to achieve the preparation of the modified carrier. Preferably, based on the weight of pseudo-boehmite as 100%, the amount of magnesium aluminum hydrotalcite added is 10% to 20%, and the preferred calcination temperature is 300°C to 600°C. The inventor optimized the dosage ratio of the two main raw materials, namely pseudo-boehmite and magnesium aluminum hydrotalcite, through a large number of experiments, and at the same time optimized the temperature range of the final calcination, and under this condition, a modified carrier with better pore structure and more suitable proportion of medium and strong acid was obtained, which showed higher mechanical properties and catalytic activity after subsequent impregnation. And, keep the muffle furnace ventilated during calcination.
[0029] In a preferred embodiment, the calcination in step S1-3 is a first-stage calcination, a second-stage calcination and a third-stage calcination, and: the temperature of the first-stage calcination is 300°C to 350°C; the temperature of the second-stage calcination is 400°C to 420°C; the temperature of the third-stage calcination is 500°C to 600°C; the time of the first-stage calcination, the second-stage calcination and the third-stage calcination is independently 2h to 4h. After a large number of experiments, the inventor designed the calcination treatment in the preparation process of the modified carrier and optimized it to a three-stage calcination, and obtained the above-mentioned progressive temperature range. Calcination under this condition can obtain a modified carrier with higher mechanical properties, more stable structure and more suitable surface acid-base activity, so that it can show higher activity when used as part of the catalyst component for the hydrodesulfurization of coal-based cracking C9+ components. In particular, during this calcination process, Mg reacts with air to obtain MgO, which can significantly improve the structure and performance of the catalyst, weaken the strong interaction between the carrier and the active component, and thus improve its catalytic activity.
[0030] In several typical embodiments, based on the weight of pseudo-boehmite as 100%, the amount of extrusion aid added is 5% to 8%, and the amount of acid solution added is 75% to 80%. Theoretically, the amount of extrusion aid and acid solution added can be adjusted according to the experimental needs, but for the above-mentioned carrier system including pseudo-boehmite and magnesium aluminum hydrotalcite provided by the present invention, the inventor has optimized the amount of extrusion aid and acid solution added through a large number of experiments, and obtained the above-mentioned range, and found that the preparation of the modified carrier according to this dosage range can more effectively optimize its pore structure and balance the acid-base center thereon, so as to obtain a modified carrier with better compatibility with active metals and higher catalytic activity. And preferably, the extrusion aid is sesbania powder and / or methyl cellulose; preferably, the mass fraction of the acid solution is 1% to 10%, and the acid solution is citric acid and / or nitric acid.
[0031] Further, in step S3, the pH adjusting agent is ammonia water. Compared with other types of alkaline agents that can be used to adjust pH, ammonia water is more suitable for the catalyst system provided by the present invention, and is easy to remove so as to reduce impurities therein. After a large number of experiments, the inventor preferably selects the impregnation in step S4 as dynamic impregnation, and the dynamic impregnation is achieved by a rotary evaporator. This impregnation method can effectively improve the distribution uniformity of active metals and the dispersibility of active metals, thereby improving its catalytic performance and extending the service life of the catalyst. The working conditions of the rotary evaporator are normal temperature and pressure. During the impregnation process, the present invention simply uses its rotation function to achieve full impregnation in the impregnation liquid without destroying the intrinsic structure of the modified carrier. Compared with the insertion of magnetic rotor stirring and ultrasonic vibration, which can also make the impregnation system dynamic, the rotary evaporator working at normal temperature and pressure can achieve dynamic impregnation, so that the impregnation liquid and the carrier are more fully in contact, thereby further improving the metal dispersibility and the activity of the catalyst finally obtained.
[0032] In several typical implementations, the impregnation time is 0.5 h to 20 h, so as to achieve sufficient impregnation, improve catalytic activity, shorten the reaction cycle, and improve commercial value.
[0033] Furthermore, for the preparation system of the above catalyst, the inventors have optimized the drying temperature of step S4 to be 100°C to 120°C and the time to be 2h to 12h after a large number of experiments; the calcination temperature is 420°C to 470°C and the time to be 2h to 3h. Under this condition, a hydrogenation catalyst for coal-based cracking C9+ components with better pore size, more stable structure and better mechanical properties is obtained.
[0034] Another aspect of the present invention provides a hydrogenation catalyst for coal-based cracking C9+ components, which is prepared by the above-mentioned preparation method. The hydrogenation catalyst obtained by the present invention not only has the above-mentioned excellent physical and chemical properties to ensure its catalytic activity, but also has the advantages of good metal dispersion, large pore volume and strong anti-carbon deposition performance, which can well meet the production quality requirements and extend the operation cycle of the device.
[0035] Furthermore, the specific surface area of the hydrogenation catalyst for coal-based cracking C9+ components is 150 g / cm 3 ~170g / cm 3 , the proportion of medium-strong acid is 45% to 55%. That is, the obtained hydrogenation catalyst has the characteristics of high specific surface area and appropriate proportion of medium-strong acid, thus showing excellent catalytic activity in the hydrodesulfurization process of coal-based cracking C9+ components, especially the effect of reducing the bromine value in coal-based cracking C9+ components is extremely significant.
[0036] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0038] Example 1
[0039] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0040] 1. Preparation of modified carrier: Take 200g of pseudo-boehmite powder, 20g of magnesium aluminum hydrotalcite powder, add 9g of sesbania powder (viscosity of 2000 centipoise), 2.4g of methyl cellulose, and mix well. Then evenly add 155g of dilute nitric acid aqueous solution, of which the mass of nitric acid is 3.0g (prepared with concentrated nitric acid with a concentration of 68%). Knead the materials for 60min, then roll them for 30min, and extrude them with a cloverleaf plate with a diameter of 1.7mm. After drying overnight at room temperature, dry them at 120℃ for 6h, and calcine them at 500℃ for 4h to obtain the modified carrier.
[0041] 2. Preparation of hydrogenation catalyst:
[0042] (1) 26.973 g of ammonium heptamolybdate, 19.5 g of nickel nitrate, and 0.1628 g of triethanolamine, wherein the molar ratio of the Mo element in the ammonium heptamolybdate to the triethanolamine is 1:0.05, are mixed to obtain a first impregnation solution;
[0043] (2) impregnating an equal volume of the modified support in the first impregnation solution, and adjusting the impregnation solution with 25% by mass ammonia water until its pH value is 9.80. The impregnation process is carried out by a rotary evaporator operating at room temperature and pressure to achieve dynamic impregnation for 0.5 h;
[0044] (3) After the impregnation, the solid catalyst was filtered and dried at 120°C overnight, and then calcined at 450°C for 2h to obtain a hydrogenation catalyst for coal-based cracking of C9+ components.
[0045] Example 2
[0046] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0047] 1. Preparation of modified carrier: Take 200g of pseudo-boehmite powder, 30g of magnesium aluminum hydrotalcite powder, add 8g of sesbania powder (viscosity of 2000 centipoise), 4g of methyl cellulose, and mix evenly. Then evenly add 160g of citric acid aqueous solution, of which the mass of citric acid is 5.0g. Knead the materials for 60min, then roll them for 30min, and extrude them with a clover plate with a diameter of 2.0mm. After drying overnight at room temperature, drying at 120℃ for 6h, calcining at 300℃ for 2h, 420℃ for 2h, and 500℃ for 4h, the modified carrier is obtained.
[0048] 2. Preparation of hydrogenation catalyst:
[0049] (1) 26.973 g of ammonium heptamolybdate, 19.5 g of nickel nitrate, and 0.1048 g of urea, wherein the molar ratio of Mo element in the ammonium heptamolybdate to urea is 1:0.08, are mixed to obtain a first impregnation solution;
[0050] (2) impregnating an equal volume of the modified support in the first impregnation solution, and adjusting the impregnation solution with 25% by mass ammonia water until its pH value is 9.80. The impregnation process is carried out by a rotary evaporator operating at room temperature and pressure to achieve dynamic impregnation for 0.5 h;
[0051] (3) After the impregnation, the solid catalyst was filtered and dried at 120°C overnight, and then calcined at 450°C for 2h to obtain a hydrogenation catalyst for coal-based cracking of C9+ components.
[0052] Example 3
[0053] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0054] 1. Preparation of modified carrier: Take 200g of pseudo-boehmite powder, 40g of magnesium aluminum hydrotalcite powder, add 10g of sesbania powder (viscosity of 2000 centipoise), 4g of methyl cellulose, and mix evenly. Then evenly add 155g of mixed aqueous solution of citric acid and nitric acid, wherein the mass of citric acid is 5.0g and the mass of nitric acid is 10.2g. Knead the materials for 60min, then roll them for 30min, and extrude them with a clover plate with a diameter of 2.0mm. After drying overnight at room temperature, drying at 120℃ for 6h, calcining at 350℃ for 2h, 400℃ for 2h, and 600℃ for 4h, the modified carrier is obtained.
[0055] 2. Preparation of hydrogenation catalyst:
[0056] (1) 26.973 g of ammonium heptamolybdate, 19.5 g of nickel nitrate, and 0.1310 g of urea, wherein the molar ratio of Mo element in the ammonium heptamolybdate to urea is 1:0.1, are mixed to obtain a first impregnation solution;
[0057] (2) impregnating an equal volume of the modified support in the first impregnation solution, and adjusting the impregnation solution with 25% by mass ammonia water until its pH value is 9.80. The impregnation process is carried out by a rotary evaporator operating at room temperature and pressure to achieve dynamic impregnation for 0.5 h;
[0058] (3) After the impregnation, the solid catalyst was filtered and dried at 120°C overnight, and then calcined at 450°C for 2h to obtain a hydrogenation catalyst for coal-based cracking of C9+ components.
[0059] Example 4
[0060] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0061] 1. Preparation of modified carrier: The modified carrier prepared in Example 3 was used.
[0062] 2. Preparation of hydrogenation catalyst:
[0063] (1) 26.973 g of ammonium heptamolybdate, 12.208 g of cobalt nitrate, and 13.089 g of citric acid, wherein the molar ratio of the Co element in the cobalt nitrate to the citric acid is 1:1, are mixed to obtain a first impregnation solution;
[0064] (2) impregnating an equal volume of the modified support in the first impregnation solution, and adjusting the impregnation solution with 25% by mass ammonia water until its pH value is 9.80. The impregnation process is carried out by a rotary evaporator operating at room temperature and pressure to achieve dynamic impregnation for 0.5 h;
[0065] (3) After the impregnation, the solid catalyst was filtered and dried at 120°C overnight, and then calcined at 450°C for 2h to obtain a hydrogenation catalyst for coal-based cracking of C9+ components.
[0066] Example 5
[0067] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0068] The only difference between this embodiment and embodiment 1 is that during the preparation of the hydrogenation catalyst, triethanolamine is replaced with an equal molar amount of oxalic acid, and other conditions remain unchanged.
[0069] Example 6
[0070] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0071] The only difference between this embodiment and embodiment 1 is that in the preparation process of the hydrogenation catalyst, triethanolamine is replaced by an equimolar amount of ammonium dihydrogen phosphate, and other conditions remain unchanged.
[0072] Example 7
[0073] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0074] The only difference between this embodiment and embodiment 1 is that during the preparation of the modified carrier, the amount of magnesium aluminum hydrotalcite powder is adjusted to 10 g, the amount of sesbania powder is adjusted to 15 g, the amount of methyl cellulose is adjusted to 5 g, and the amount of dilute nitric acid aqueous solution is adjusted to 170 g, while other conditions remain unchanged.
[0075] Example 8
[0076] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0077] The only difference between this embodiment and embodiment 1 is that during the preparation of the modified carrier, the amount of magnesium aluminum hydrotalcite powder is adjusted to 50 g, the amount of sesbania powder is adjusted to 4 g, the amount of methyl cellulose is adjusted to 2 g, and the amount of dilute nitric acid aqueous solution is adjusted to 140 g, while other conditions remain unchanged.
[0078] Example 9
[0079] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0080] The only difference between this embodiment and embodiment 1 is that in the preparation process of the hydrogenation catalyst, the calcination conditions in step (3) are 400° C. and 4 h.
[0081] Example 10
[0082] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0083] The only difference between this embodiment and embodiment 1 is that in the preparation process of the hydrogenation catalyst, the calcination conditions of step (3) are 500° C. for 1 h.
[0084] Embodiment 11
[0085] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0086] The only difference between this embodiment and embodiment 1 is that in the preparation process of the hydrogenation catalyst, dynamic impregnation is not used in step (2), but the impregnation system containing the modified carrier is directly left to stand to complete the impregnation.
[0087] Example 12
[0088] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0089] The only difference between this embodiment and embodiment 1 is that in the preparation process of the hydrogenation catalyst, the dynamic impregnation in step (2) is achieved by adding a magnetic rotor to the impregnation system to stir the mixed system, and the stirring speed is 300 rpm.
[0090] Embodiment 13
[0091] A method for preparing a hydrogenation catalyst for coal-based cracking of C9+ components:
[0092] The only difference between this embodiment and embodiment 1 is that during the preparation of the modified carrier, the calcination condition is 600° C. for 1 h.
[0093] Comparative Example 1
[0094] A method for preparing a hydrogenation catalyst:
[0095] The only difference between this comparative example and Example 1 is that in the preparation process of the hydrogenation catalyst, no modified carrier is used, but an alumina carrier commonly used in the art is directly used.
[0096] Comparative Example 2
[0097] A method for preparing a hydrogenation catalyst:
[0098] The only difference between this comparative example and Example 1 is that no organic complexing agent is added during the preparation of the hydrogenation catalyst.
[0099] Comparative Example 3
[0100] A method for preparing a hydrogenation catalyst:
[0101] The only difference between this comparative example and Example 1 is that during the preparation of the hydrogenation catalyst, the pH value of the impregnation solution containing the modified support is not adjusted, but it is directly subjected to dynamic impregnation.
[0102] Comparative Example 4
[0103] A method for preparing a hydrogenation catalyst:
[0104] The only difference between this comparative example and Example 1 is that in the preparation process of the hydrogenation catalyst, the molar ratio of the Mo element to triethanolamine in step (1) is adjusted to 1:0.01.
[0105] Comparative Example 5
[0106] A method for preparing a hydrogenation catalyst:
[0107] The only difference between this comparative example and Example 1 is that in the preparation process of the hydrogenation catalyst, the molar ratio of the Mo element to triethanolamine in step (1) is adjusted to 1:2.
[0108] Comparative Example 6
[0109] A method for preparing a hydrogenation catalyst:
[0110] The only difference between this comparative example and Example 1 is that in the preparation process of the hydrogenation catalyst, the second active metal nickel nitrate is not added in step (1).
[0111] Test Method
[0112] Compressive strength: Determine the compressive strength according to GB 10505.1-1989 3A molecular sieve crushing strength determination method.
[0113] Specific surface area: Refer to GB / T19587-2017 gas adsorption BET method to determine the specific surface area of solid substances.
[0114] Pore volume: refer to GB / T21650.3-2011 mercury intrusion method and gas adsorption method to determine the pore size distribution and porosity of solid materials.
[0115] Acid content and proportion of medium-strong acid content: Refer to ASTM D4824-2024 for the standard test method for determining catalyst acidity using ammonia chemical adsorption method. The temperature-programmed desorption method (TPD) is an effective means to characterize the surface acidity of solid acids. Its determination of acidity is based on the basic principle that the activation energy of the acidic catalyst surface for alkaline adsorbates is different and the desorption temperature is also different. It quantitatively determines the amount of acid on the surface of the solid catalyst and qualitatively analyzes the acid strength. Taking NH3 as an example, the principle and steps of the temperature-programmed desorption method are as follows: the NH3-saturated sample is heated at low temperature in vacuum to remove physically adsorbed NH3 molecules, the sample is placed in an inert gas and heated at a certain rate, and at a certain temperature, the adsorbate is detached from the adsorption center, that is, the NH3 bound to the acid center is desorbed. The desorption temperatures of the adsorbates of active centers with different acid strengths are generally different. The concentration of the desorbed NH3 gas is monitored as a function of the sample temperature to obtain a desorption spectrum consisting of one or more peaks, which is called a TPD graph. The temperature corresponding to the maximum peak intensity of each TPD peak in the figure is called the peak temperature. The peak temperature characterizes the strength of the acid center of the sample, and the peak area represents the acid amount, which is proportional to the acid amount. The results of TPD are related to sample pretreatment, program heating rate, reactor and carrier gas flow rate, etc. Generally, the desorption peak below 200°C is attributed to weak acid sites, the desorption peak between 200°C and 500°C is defined as medium-strong acid sites, and the desorption peak above 500°C is attributed to strong acid sites. The more medium-strong acid content in the catalyst, the more active sites the catalyst will form. Strong acid is not conducive to the formation of more active sites. The more active sites, the higher the hydrogenation activity of the catalyst, which makes the oil hydrodesulfurization rate high.
[0116] The above performance tests were performed on the modified supports and hydrogenation catalysts obtained in the examples and comparative examples, and the results are shown in Tables 1 and 2.
[0117] Table 1
[0118]
[0119]
[0120] Among the embodiments and comparative examples not listed in the table, Embodiment 5, Embodiment 6, Embodiment 9 to Embodiment 12, and Comparative Examples 2 to Comparative Examples 6 and Embodiment 1 use the same modified carrier, and their physicochemical properties are the same; the modified carrier used in Embodiment 4 is the same as that in Embodiment 3.
[0121] Table 2
[0122]
[0123]
[0124] The hydrogenation catalysts obtained in the examples and comparative examples were subjected to a hydrodesulfurization activity evaluation test. The evaluation experiment was carried out on a 100 mL small fixed-bed hydrogenation device, and the catalysts were presulfurized before the evaluation.
[0125] Presulfidation conditions: The reactor is heated from room temperature to 150℃~200℃ (bed temperature) at 10℃ / h~20℃ / h, and the temperature is kept constant for 4~8 hours. Then, sulfurized oil is added, and the temperature is raised to 320℃~360℃ at 5℃ / h~10℃ / h, and the temperature is kept constant for 4~8 hours. During this period, the reaction system pressure is 2.8MPa~3.2MPa, and the liquid hourly volume space velocity is 1.0h -1 ~2.0h -1 , hydrogen-oil volume ratio (200-600): 1, the vulcanizing agent is carbon disulfide or dimethyl disulfide.
[0126] Evaluation conditions: total reaction pressure 2.8MPa~3.2MPa, liquid hourly volume space velocity 0.5h -1 ~1.0h -1 , hydrogen-oil volume ratio 200-600:1, reaction temperature 300℃-320℃.
[0127] Evaluation raw materials: coal-based C9+ component oil.
[0128] The results of the activity evaluation are shown in Table 3.
[0129] Table 3
[0130]
[0131]
[0132] From the above description, it can be seen that the above embodiments of the present invention achieve the following: 1. When the alkaline earth metal Mg is added in the form of hydrotalcite during the preparation of the carrier, the strong interaction between the carrier and the active component can be weakened, making the active metal easy to activate. 2. On the one hand, triethanolamine, urea and citric acid increase the solubility of the active metal, and the active metal can be fully loaded with one-step impregnation; on the other hand, the interaction between the active component and the carrier is weakened, so that more hydrogenation centers are formed on the catalyst carrier, the effective utilization rate of the active component is increased, and the hydrogenation desulfurization performance of the catalyst is improved. 3. The use of dynamic impregnation prevents uneven distribution of active metals, which is beneficial to improving the dispersibility of active metals and thus improving catalytic performance.
[0133] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrogenation catalyst for coal-based cracking C9+ components, characterized in that: include: Step S1, preparing a modified carrier, wherein the modified carrier includes pseudo-boehmite and magnesium-aluminum hydrotalcite; Step S2, preparing a first impregnation solution and adding the modified support thereto, wherein the first impregnation solution includes an active metal element and an organic complexing agent; Step S3, adding a pH adjuster to the first impregnation liquid to obtain a second impregnation liquid with a pH of 9 to 11; Step S4, impregnating the modified carrier in the second impregnation solution, and obtaining the hydrogenation catalyst for coal-based cracking C9+ components after solid-liquid separation, drying and roasting; The active metal element includes Mo and at least one transition metal element other than Mo, and the molar ratio of the active metal element to the organic complexing agent is 1:(0.02-1.5).
2. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to claim 1, characterized in that: The organic complexing agent is selected from one or more of urea, triethanolamine and citric acid, and the transition metal is selected from one or more of Ni, Co and Zn.
3. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to claim 2, characterized in that: The active metal elements are Mo and Ni, the organic complexing agent is triethanolamine and / or urea, and the molar ratio of Mo to triethanolamine and / or urea is 1:(0.05-0.1); or, the active metal elements are Mo and Co, the organic complexing agent is citric acid, and the molar ratio of Co to citric acid is 1:(0.1-1).
4. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to any one of claims 1 to 3, characterized in that: Step S1 also includes: Step S1-1, uniformly mixing the pseudo-boehmite, the magnesium-aluminum hydrotalcite and an extrusion aid to obtain a first mixed material; Step S1-2, adding acid solution to the mixed material to obtain a second mixed material; Step S1-3, the second mixed material is sequentially molded, dried and calcined to obtain the modified support; Preferably, the amount of the magnesium-aluminum hydrotalcite added is 10% to 20% based on 100% weight of the pseudo-boehmite; Preferably, the calcination temperature is 300°C to 600°C.
5. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to claim 4, characterized in that: The calcination in step S1-3 is a first-stage calcination, a second-stage calcination and a third-stage calcination performed sequentially, and: The temperature of the first stage calcination is 300°C to 350°C; The temperature of the second stage calcination is 400°C to 420°C; The temperature of the three-stage calcination is 500°C to 600°C; The time of the first-stage calcination, the second-stage calcination and the third-stage calcination is independently 2 hours to 4 hours.
6. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to claim 4 or 5, characterized in that: Based on the weight of the pseudo-boehmite being 100%, the amount of the extrusion aid added is 5% to 8%, and the amount of the acid solution added is 75% to 80%; Preferably, the extrusion aid is sesbania powder and / or methylcellulose; Preferably, the mass fraction of the acid solution is 1% to 10%, and the acid solution is citric acid and / or nitric acid.
7. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to any one of claims 1 to 6, characterized in that: The pH regulator in step S3 is aqueous ammonia; The impregnation in step S4 is dynamic impregnation, and the dynamic impregnation is achieved by using a rotary evaporator.
8. The method for preparing a hydrogenation catalyst for coal-based cracking C9+ components according to any one of claims 1 to 7, characterized in that: In step S4, The drying temperature is 100°C to 120°C and the drying time is 2h to 12h; The calcination temperature is 420° C. to 470° C., and the calcination time is 2 h to 3 h.
9. A hydrogenation catalyst for coal-based cracking of C9+ components, characterized in that: The hydrogenation catalyst for coal-based cracking of C9+ components is prepared by the preparation method of the hydrogenation catalyst for coal-based cracking of C9+ components described in any one of claims 1 to 8.
10. The hydrogenation catalyst for coal-based cracking C9+ components according to claim 9, characterized in that: The specific surface area of the hydrogenation catalyst for coal-based cracking C9+ components is 150 g / cm 3 ~170g / cm 3 , the proportion of medium and strong acids is 45% to 55%.
